2007
DOI: 10.1007/s10549-007-9820-4
|View full text |Cite
|
Sign up to set email alerts
|

NBS1 variant I171V and breast cancer risk

Abstract: The NBS1/p95 protein has a pivotal role in the sensing and repair of chromosome breaks. A missense mutation in the NBS1 gene, I171V, has recently been associated with a ninefold increased risk of breast cancer in Polish patients. Positive associations have also been reported for leukaemia and larynx cancer suggesting that I171V could be a more general susceptibility factor for malignancies. We investigated the prevalence of this mutation in two large hospital-based case-control series from Germany and from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Genes correlated with breast cancer susceptibility include also the ''guardian of the genome'' TP53, and genes of proteins from p53-DNA repair-pathways-the PTEN (phosphatase and tensin homolog, also called mutated in multiple advanced cancers 1) gene, and the CHEK2 (protein kinase CHK2 isoform c) gene. Recent studies have revealed new breast cancer markers like NBS1/p95 [29] and PALB2. PALB2 protein interacts with BRCA2, and is involved in homologous recombination and the repair of DNA double-strand breaks [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Genes correlated with breast cancer susceptibility include also the ''guardian of the genome'' TP53, and genes of proteins from p53-DNA repair-pathways-the PTEN (phosphatase and tensin homolog, also called mutated in multiple advanced cancers 1) gene, and the CHEK2 (protein kinase CHK2 isoform c) gene. Recent studies have revealed new breast cancer markers like NBS1/p95 [29] and PALB2. PALB2 protein interacts with BRCA2, and is involved in homologous recombination and the repair of DNA double-strand breaks [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 192 women with no personal or family history of cancer were enrolled as normal control from Cancer Hospital of Fudan University between 2003 and 2007. This project has been approved by the Scientific and Ethical Committee of the Cancer Hospital of Fudan University.Oligonucleotide primers and polymerase chain reaction (PCR) conditions as former publications were used to amplify the specific segments which spanned the three mutation spots (RAD50 687delT, NBS1 657del5 and NBS1 I171 V) [3,5,6]. The PCR and DNA sequencing analysis were performed as described previously [4].…”
mentioning
confidence: 99%
“…However, other groups did not find a similar association in European patients with breast cancer, leukemia, or lymphoma (29)(30)(31). It remains unclear whether this particular polymorphic variant of the NBS1 gene is associated with cancer.…”
Section: Nbs1-i171v Polymorphic Variant Increases the Risk Of Breast mentioning
confidence: 92%